Bone marrow stromal cells in Modic type 1 changes promote neurite outgrowth - Mengis, Tamara; Herger, Nick; Heggli, Irina; Devan, Jan; Spirig, José Miguel; Laux, Christoph J.; Brunner, Florian; Farshad, Mazda; Distler, Oliver; Dudli, Stefan (Frontiers in Cell and Developmental Biology, 2023)
The pain in patients with Modic type 1 changes (MC1) is often due to vertebral body endplate pain, which is linked to abnormal neurite outgrowth in the vertebral body and adjacent endplate. In this study, the aim was to understand the role of MC1 bone marrow stromal cells (BMSCs) in neurite outgrowth. BMSCs can produce neurotrophic factors, have been shown to be pro-fibrotic in MC1, and expand in the perivascular space where sensory vertebral nerves are located. The study involved the exploration of the BMSC transcriptome in MC1, co-culture of MC1 BMSCs with the neuroblastoma cell line SH-SY5Y, analysis of supernatant cytokines and analysis of gene expression changes in cocultured SH-SY5Y. Transcriptomic analysis revealed upregulated brain-derived neurotrophic factor (BDNF) signaling-related pathways. Co-cultures of MC1 BMSCs with SH-SY5Y cells resulted in increased neurite sprouting compared to co-cultures with control BMSCs. The concentration of BDNF and other cytokines supporting neuron growth were increased in MC1 vs. control BMSCs co-cultures supernatants. Together, these findings show that MC1 BMSCs provide strong pro-neurotrophic cues to nearby neurons and could be a relevant disease-modifying treatment target.